Development of Children's Ability to Recognize Letters Through Unscrambled Words at BIAS Kindergarten Yogyakarta - Adin Suryadin; Rz. Ricky Satria Wiranata; M. Sayyidul Abrori (Journal of Childhood Development, 2021)
The development of children's ability to recognize letters at the beginning of entering the B1 kindergarten class is still low. The purpose of this study was to improve children's ability to recognize letters through word deciphering games. The research method used is classroom action research, with the research subject of the BI group at the Integrated Islamic Kindergarten of Bina Anak Sholeh Yogyakarta. The technique in collecting data is in the form of observation, which is processed by the percentage technique. The results of the research in each cycle have shown an increase in the ability of children to recognize letters from the initial conditions, cycle I to cycle I. Thus it can be concluded that word deciphering games can improve children's ability to recognize letters.